The Penerimaan Moderasi Beragama Bagi Masyarakat Post Covid - Norma Fitria; Fridiyanto Fridiyanto (Postgraduate State Islamic Institute (IAIN) Metro, 2021)
This article aims to find out the overall results of several previous research reviews. The result of the discussion in this article is the emergence of a broad understanding of the community in knowing the resolution of a disputed problem. Religious moderation after COVID-19, Muslims in Indonesia need to review religious views or rules. Because Islamic law has flexibility which is a view that we must practice, so to follow up on the above is an obligation to protect ourselves or our souls from all threats of danger